The Inhibition of Tobamovirus by Using the Extract of Banana Flower - Nurviani Nurviani; Susamto Somowiyarjo; Sri Sulandari; Siti Subandiyah (Jurnal Perlindungan Tanaman Indonesia, 2018)
Some extract of the banana plants parts have been identified to produce a compound that has efficacy as traditional medicine and human virus inhibitor. There was no previous report  on the use of the banana flower as the plants antiviral sources for plant pathogen. The objective of this study was to identify the potency  of two types of the banana flower as the Tobamovirus inhibitor substance. The antiviral was prepared from the extract of Ambon banana (Musa acuminata Colla) flower and Klutuk banana (Musa balbisiana Colla) flower, as the comparison extract of Mirabilis jalapa L. leaf which is widely known to have antiviral on various plant viruses was used. This study applied the Complete Randomized Design with three replications. Collected data includes the virus incubation period and the inhibitor power upon the local necrotic symptom on indicator plant. Results of this study showed that the extract of Ambon and Klutuk banana flower was able to inhibit the Tobamovirus with inhibition levels of 86.34% and 91.22%.IntisariBeberapa ekstrak bagian tanaman pisang diketahui memiliki kandungan senyawa yang berkhasiat sebagai obat tradisional dan zat yang dapat menghambat virus manusia. Belum pernah dilaporkan penggunaan bunga pisang sebagai sumber antiviral terhadap virus tumbuhan. Penelitian ini bertujuan untuk mengetahui potensi ekstrak bunga dua jenis pisang sebagai zat penghambat Tobamovirus. Antiviral disiapkan dari ekstrak bunga pisang Ambon (Musa acuminata Colla) dan pisang Klutuk (Musa balbisiana Colla), sebagai pembanding digunakan ekstrak daun Mirabilis jalapa L. yang sudah banyak diketahui mengandung antiviral pada berbagai virus tumbuhan. Penelitian ini dirancang menggunakan Rancangan Acak Lengkap dengan 3 ulangan. Data yang dikumpulkan meliputi masa inkubasi virus dan daya hambat gejala nekrotik lokal pada tanaman indikator. Hasil penelitian menunjukkan bahwa ekstrak bunga pisang jenis Ambon dan Klutuk mampu menghambat Tobamovirus dengan tingkat penghambatan sebesar 86,34% dan 91,22%.